Comparison of osseous healing after sagittal split ramus osteotomy and intraoral vertical ramus osteotomy. Issue 10 (October 2018) - Rokutanda, S.; Yamada, S.; Yanamoto, S.; Omori, K.; Fujimura, Y.; Morita, Y.; Rokutanda, H.; Kohara, H.; Fujishita, A.; Nakamura, T.; Yoshimi, T.; Yoshida, N.; et al.
Abstract: The sagittal split ramus osteotomy (SSRO) is generally associated with greater postoperative stability than the intraoral vertical ramus osteotomy (IVRO); however, it entails a risk of inferior alveolar nerve damage. In contrast, IVRO has the disadvantages of slow postoperative osseous healing and projection of the antegonial notch, but inferior alveolar nerve damage is believed to be less likely. The purposes of this study were to compare the osseous healing processes associated with SSRO and IVRO and to investigate changes in mandibular width after IVRO in 29 patients undergoing mandibular setback. On computed tomography images, osseous healing was similar in patients undergoing SSRO and IVRO at 1 year after surgery. Projection of the antegonial notch occurred after IVRO, but returned to the preoperative state within 1 year. The results of the study indicate that IVRO is equivalent to SSRO with regard to both bone healing and morphological recovery of the mandible.